A Texas Ranger - Raine, William MacLeod, 1871-1954 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Texas Ranger" by William MacLeod Raine is a novel set in the early 20th century that captures the rugged atmosphere of the American West. The story intricately explores themes of honor, justice, and human connection against the backdrop of a lawless frontier. Central to the narrative is the character of a young ranger, Lieutenant Steve Fraser, who embodies the ideals of bravery and justice as he navigates a world filled with outlaws, frontier folk, and the complexities of personal relationships with women like Margaret Kinney. The opening of the book introduces a tense situation where a young woman, Margaret Kinney, attempts to commandeer a wagon from a stranger in a desperate bid to aid her wounded brother, a fugitive from justice. Their tense interaction quickly escalates into a struggle for power, revealing both characters' fierce determination and vulnerabilities. Just as she finds herself at the mercy of the stranger, a violent encounter unfolds nearby, involving a dangerous convict. Amid this chaos, the story lays the groundwork for themes of sacrifice and resilience as the characters are thrust into a thrilling conflict that ultimately challenges their beliefs about loyalty, identity, and redemption. (This is an automatically generated summary.)
Release date is 2004-01-01
Produced by Jim Weiler and David Widger
Keywords: Western stories; Texas -- Fiction